2008
DOI: 10.1016/j.hrthm.2008.02.025
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin-aldosterone system (RAAS) and cardiac arrhythmias

Abstract: The role of the renin-angiotensin-aldosterone system (RAAS) in many cardiovascular disorders, including hypertension, cardiac hypertrophy, and atherosclerosis is well established, whereas its relationship with cardiac arrhythmias is a new area of investigation. Atrial fibrillation and malignant ventricular tachyarrhythmias, especially in the setting of cardiac hypertrophy or failure, appear to be examples of RAAS-related arrhythmias, since treatment with RAAS modulators, including angiotensin converting enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 79 publications
2
86
0
3
Order By: Relevance
“…Recent research has shown that activation of RAAS is important for AF. [33][34][35] RAAS is the key mechanism of atrial remodeling, which is believed to be the main cause of AF. The ACE I/D gene polymorphisms are related to the activity of angiotensin, which is the main effective component of the RAAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that activation of RAAS is important for AF. [33][34][35] RAAS is the key mechanism of atrial remodeling, which is believed to be the main cause of AF. The ACE I/D gene polymorphisms are related to the activity of angiotensin, which is the main effective component of the RAAS.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the serum levels of the different components of RAAS in heart failure patients has been suggested as a guide to tailor individual therapy (Emdin et al 2015). RAAS activation also seems to be arrhythmogenic, and this goes especially for atrial fibrillation (Iravanian and Dudley 2008). In this case, RAAS activation may lead to alterations in ion channels through increasing oxidative stress.…”
Section: Neurohormonal Signalingmentioning
confidence: 99%
“…Angiotensin II (ANG II), formed locally by mast cell-derived renin in myocardial ischemia (Mackins et al, 2006;Reid et al, 2007), is a major NHE activator via ANG II type 1 receptors (AT 1 Rs) (Reid et al, 2004) and only a minor, indirect inhibitor via AT 2 receptors (Avkiran and Haworth, 2003). ANG II elicits reperfusion arrhythmias by a direct action (Harada et al, 1998;Yahiro et al, 2003;Iravanian and Dudley, 2008), as well as by facilitating NE release (Schömig, 1990;Meredith et al, 1991;Levi and Smith, 2000); both of these actions are AT 1 Rmediated .…”
Section: Introductionmentioning
confidence: 99%